Design, synthesis and biological evaluation of novel hydrogen sulfide releasing capsaicin derivatives. Issue 9 (15th May 2018) - Gao, Mingxiang; Li, Jinyu; Nie, Cunbin; Song, Beibei; Yan, Lin; Qian, Hai
Graphical abstract: A series of new hybrids of capsaicin or dihydrocapsaicin bearing various H2 S-releasing moieties were prepared and evaluated in an effort to improve the activity of CAP and alleviate its irritating effects. Abstract: Capsaicin (CAP), the prototypical TRPV1 agonist, is the major active component in chili peppers with health-promoting benefits. However, its use is limited by the low bioavailability and irritating quality. In this study, for improving the activity of CAP and alleviating its irritating effects, a series of H2 S-releasing CAPs were designed and synthesized by combining capsaicin and dihydro capsaicin with various hydrogen sulfide donors. The resulting compounds were evaluated their TRPV1 agonist activity, analgesic activity, anticancer activities, H2 S-releasing ability, and gastric mucosa irritation. Biological evaluation indicated that the most active compoundB9, containing 5-(4-hydroxyphenyl)-3 H -1, 2-dithiole-3-thione moiety as H2 S donor, had better analgesic activity and displayed more potent cytotoxic effects on the test cell lines than the lead compound CAP. Furthermore, the preferred compound, B9 reduced rat gastric mucosa irritation caused by CAP. Notably, the improved properties of this derivative are associated with its H2 S-releasing capability.